1993
DOI: 10.2175/wer.65.7.9
|View full text |Cite
|
Sign up to set email alerts
|

Importance of phase behavior on the removal of residual DNAPLs from porous media by alcohol flooding

Abstract: zyxwvutsrqponmlkjihgfedcbaZYXWVUTSRQPONMLKJIHGFEDCBA A promising method of accelerating the removal of residual DNAPLs from aquifers involves the mobilization of trapped globules by alcohol flooding. This technology was originally developed in the petroleum industry for the recovery of residual oil after waterflooding. Alcohols can significantly reduce the interfacial tension between the residual DNAPLs and the aqueous phase, allowing for mobilization of trapped globules through pore constrictions. In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(53 citation statements)
references
References 19 publications
1
52
0
Order By: Relevance
“…For example, remediation techniques for groundwater and soil contaminated by nonaqueous phase liquids (NAPLs), often employ surfactants to reduce surface tension and enhance mobilization of NAPLs [Mason and Kueper, 1996;Fortin et al, 1997], or employ cosolvents and humic substances to increase the solubility of slightly soluble NAPLs [Brandes and Farley, 1993;Li et al, 1996;Tatalovich et al, 2000]. Furthermore, bioremediation techniques employ bacteria that enhance contaminant degradation [Chaudhry, 1994].…”
Section: Introductionmentioning
confidence: 99%
“…For example, remediation techniques for groundwater and soil contaminated by nonaqueous phase liquids (NAPLs), often employ surfactants to reduce surface tension and enhance mobilization of NAPLs [Mason and Kueper, 1996;Fortin et al, 1997], or employ cosolvents and humic substances to increase the solubility of slightly soluble NAPLs [Brandes and Farley, 1993;Li et al, 1996;Tatalovich et al, 2000]. Furthermore, bioremediation techniques employ bacteria that enhance contaminant degradation [Chaudhry, 1994].…”
Section: Introductionmentioning
confidence: 99%
“…A number of laboratory studies have examined the dissolution and mobilization of NAPL by cosolvents (Luthy et al, 1992;Brandes and Farley, 1993;Luthy, 1993, 1994;Milazzo, 1993;Imhoff et al, 1995;Roy et al, 1995;Kueper, 1996, 1997). These studies have shown that NAPL may be effectively removed using cosolvents such as alcohols.…”
Section: In-situ Flushing Technologymentioning
confidence: 99%
“…A number of laboratory studies have examined the dissolution and mobilization of NAPLs by cosolvents [Luthy et al, 1992; Brandes and Farley, 1993;Luthy, 1993, 1994;Milazzo, 1993 …”
Section: Introductionmentioning
confidence: 99%